Perceptual Assimilation of SSBE Vowels by Tertiary-Level Bulgarian Students (Philologia, 2021)
The paper presents the results of a Perceptual Assimilation Task whose aim was to assess and establish the perceptual similarity of SSBE and Bulgarian vowel categories as heard by experienced Bulgarian tertiary-level students and to relate them to those predicted by the articulatory-phonetic similarities between the vowel systems of the two languages. The PAT showed that the participants were able to fit all English vowels into Bulgarian categories, using any detected quantitative, qualitative or feature similarities. The results showed that PAM accounts for the assimilation patterns of most English vowels, which were mapped to PAM assimilation types. The study is designed to help further research that examines the production patterns of SSBE and Bulgarian vowels by these same students to determine to what extent the perceptual assimilation patterns can predict difficulties L2 learners encounter in the acquisition of the vowel sounds of Standard Southern British English.
Keywords: perceptual assimilation; categorisation; vowels; assimilation type; goodness of fit